(untitled) (Archives of Criminology, 2008)
The author is looking for the origins of crime in the conflict between those who legally possess power and have access to resources and others, who have no power and are deprived of most of the important resources. He brings up evidence suggesting that the societies with the highest rates of crime are also those with the highest levels of inequality. The author tries to answer two questions: how can crime be prevented(primary prevention) and how can the likelihood of its happening again be reduced (preventing re-offending), in both an effective and ethical way. The author states that the ideal method of preventing the crime is not the threat of potential punishment, but social crime prevention, such as more equitable distribution of material goods, which would encourage people to live a rewarding life without harming others. Further, the author discusses the advantages of the restorative system over the conventional one in terms of ‘preventing re-offending’: focussing on the harm that is caused rather than on the laws that are broken, giving victims a chance to express their fear and needs as well as giving perpetrators the possibility to explain their reasons and express their needs, which enables reflection on how to put everything right and how to engage the community.